Pecularities of calculation of throughput capacity and energy consumption of oil pipeline at parallel operation of pumping units - Serediuk, M.D. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
The peculiarities of hydrodynamic processes in the case of parallel operation of centrifugal pumps on the pipeline are established. The method and software for determining the throughput capacity and energy efficiency of the main oil pipeline for the use of multi-type pumps operating at oil pumping stations are developed. It has been proved by calculations that, under certain conditions, a parallel operation of the pumps can have advantages over the traditional sequential scheme of their operation.